Efforts to Improve Reading Ability Through Literacy Learning (Studies on Students at the Catholic Elementary School of ST. Vincentius Noongan) - Hamsah, Hamsah; Mesra, Romi; Jannah, Miftahul; Bagit, Juanito; Kiwo, Rodi; Swabra, Metelda; Manurung, Lolita (Technium Social Sciences Journal, 2023)
The goal of this research was to discover how teaching literacy might improve the reading abilities of Class IV pupils at St.Vincentius Noongan Catholic Elementary School. We can increase kids’ comprehension of reading texts and help them read correctly through literacy learning. The sort of study that will be employed is class action research (CAR). Classroom action research is carried out in order to solve issues and enhance teaching quality. Teachers do a sort of study known as classroom action research to solve issues in their classrooms. The goal of this study is to present a summary of the advancement of students’ reading outcomes through literacy learning for students in St. Catholic Elementary School’s class IV. Noongan, Vincentius. This classroom action research (CAR) includes four processes: preparation, activity, observation, and reflection. The findings of this study demonstrate the importance of the teacher’s involvement in enhancing literacy learning for children so that they can accurately interpret the text, as well as the role of parents of kids after school. pupils’ parents must also assess what their children may learn at school, such as the assignments assigned by the instructor, so that pupils always have parental support for the necessity of solid reading abilities.